Rahasia Bandung, Jejak leluhur dari Fujian sampai ke tanah Parahyangan. (The secret ancestor artefacts in Bandung, from FuJian down to Priangan) - Tan Soey Beng (Jurnal Sosioteknologi, 2015)
Although Tan Nyim Tjoy as a chinese village master (wijkmeester) of Citepus in Bandung in the year of 1914 has been mention alot in the studies of chinese history in Bandung, his grave has never been found. Nevertheless Sim Cong alley and Sim Cong primary school are well known in that area. The question is whether they are the same person pronounced in different dialect. To solve that problem a study was conducted to find out some answers in his artefacts that could be found in the tombstone of his relatives or elsewhere and orally as well as written notes of his decendants. Results showed that the question can not be answered but Tan Sim Tjong allegedly was the Chinese village master and known to his descendents by that name, on the other hand official records wrote his name as Tan Nyim Tjoy, possibly the same person. His ancestor could be traced back to Nan Jing village in Fu Jian province who migrated to Southeast Asia. Tan Hwie Tjeng was recorded as the first known ancestor that settled down in Batang in central Java for several generations before moving westward to Cirebon and Jamblang, his descendents became prominent bussinessmen and leaders in that area and gained a substantial wealth. Tan Sim Tjong dan Tan Sim Sioe moved from Cirebon to Bandung and settled down in Citepus as "the great post way" and the city of Bandung was established. Tan Sim Tjong was later possibly appointed as the Chinese village master. Their bussinesses were also successful in Bandung and their descendants not only moved eastward to settle down in eastern Priangan areas such as Garut, Tasikmalaya and Ciamis but to other cities as well such as Cimahi, Bandung, Cirebon, Tegal, Pekalongan and Jakarta. Great global economic depression in 1929 followed by world war second and Indonesia independent war wipe out most of the wealth. Several riots that followed increase the diaspora among their descendants.Nama Tan Nyim Tjoy sebagai wijkmeester Citepus tahun 1914 banyak disebut dalam berbagai tulisan mengenai sejarah kota Bandung tetapi tidak pernah disebutkan letak makamnya. Sebaliknya nama gang Sim Cong di Citepus dan SR/SDN Sim Cong dikenal oleh semua orang di daerah Citepus Bandung. Penelusuran artefak kota Bandung dan wawancara terhadap para keturunannya memperlihatkan bahwa kemungkinan yang benar adalah Tan Sim Tjong sebagai wijkmeester Citepus karena makamnya dapat ditemukan begitu juga rumahnya dan jejak    keturunannya tapi dokumen resmi menuliskan namanya sebagai Tan Nyim Tjoy, mungkin kedua nama itu adalah orang yang sama. Bahkan asal usul leluhurnya dapat ditelusuri sampai ke kampung Nan Jing diprovinsi Fu Jian, leluhurnya  berpindah ke Asia Tenggara, Tan Hwie Tjeng adalah salah satu leluhur yang tercatat menetap di Batang di pesisir utara Jawa tengah untuk beberapa generasi lalu berpindah ke Cirebon dan Jamblang di sana berkembang menjadi pedagang dan pemimpin masyarakat Tionghoa di Cirebon. Tan Sim Tjong dan Tan Sim Sioe pindah ke Bandung dengan dibangunnya "Groote Postweg" dan sukses sebagai pengusaha dan memimpin pecinan Citepus, Tan Sim Tjong diduga diangkat sebagai wijkmeester. Keturunan mereka berpindah kearah timur bermukim di kota Garut, Tasikmalaya dan Ciamis juga di kota lain seperti Cimahi, Bandung, Cirebon, Tegal, Pekalongan dan Jakarta.  Depresi ekonomi global tahun 1929 disusul Perang Dunia kedua dan perang Kemerdekaan menghancurkan sebagian besar kekayaannya sedangkan kerusuhan2 semasa republik mendorong terjadinya diaspora diantara keturunan mereka.Kata kunci: migrasi, pecinan, peranakan, Cirebon, Batang, Tasikmalaya, Jamblang, Citepus, geneology.